Efeito do uso da terra no amortecimento de cheias em reservatórios de retenção: Estudo de caso do lago azul, cidade de rio claro (sp-brasil) - Moraes, Isabel Cristina [UNESP]; Da Conceição, Fabiano Tomazini [UNESP]; Lupinacci, Cenira Maria [UNESP]; Moruzzi, Rodrigo Braga [UNESP] (My University, 2016)
This article aimed to evaluate the effect of land use on the retention reservoir performance in terms of damping floods. To this end, it was studied the Lago Azul reservoir, located at the spring water of Servidão stream, urban area of Rio Claro city (SP-Brazil). From the aerial photos classification on Geographic Information Systems-GIS, it was performed the mapping of land use to the 1958, 1972 and 2006 scenarios. The several rains were determined from the equation that relates intensity, duration and frequency of the municipality rainfall, using return periods (RP) of 5, 10, 20 and 50 years and rain time of 1 hour. The model Soil Conservation Service-SCS (1986) was used for obtaining the excess rain. The hydraulic and hydrologic modeling was used for the hydrograph spread aiming to evaluate the impacts of urban expansion in the hydrological performance of the reservoir drainage area. In 1972, flood situations occurred just to RP 20 and 50. However, in 2006 scenario, the reservoir retention capacity was insufficient, resulting in flood situations to all RP. The hydrograms obtained showed that, despite the damping of floods by the reservoir, the growth of impermeable areas increased the flow rates and caused the anticipation of wavefloods peaks. The results show that the use of reservoir for damping floods purposes should be performed as part of a series of actions among them the planning of occupation and land use.
Effect of land use on the retention reservoir performance in damping floods: A case study of the Lago Azul, Rio Claro city (SP-Brazil)